Finance Capitalism: A Look at the European Financial Accounts - Cingolani, Massimo (Panoeconomicus, 2013)
The paper explores the financial accounts database of Eurostat, a rich set of data that is largely unexploited. It describes the main financial developments at EU level during the 1990-2010 period, both in terms of institutional agents and financial products. The paper provides evidence on the consequences of asset price inflation for wealth distribution between institutional agents and argues that the conceptual scheme of the “double monetary circuit” of existing and recycled savings helps in describing and explaining the observed patterns of financialisation.Key words: Europe, Asset price inflation, Income distribution.JEL: E01, N100, N200, D530, E440, G010.